Batman, the Dark Knight returns - Miller, Frank 1957- (DC Comics, 2002)
Ten years after his retirement, a troubled Batman returns to the streets, evening the score with criminals in an increasingly violent manner, which brings trouble from the police and a gang called the Mutants and a conflict with Superman.
"Originally published in single magazine form as Batman, the Dark Knight returns 1-4.
Keywords: Batman -- Fiktive Gestalt; Batman (Personnage fictif) - Bandes dessinées; Graphic novels; Batman (Fictitious character) -- Fiction; Comic; Comic books, strips, etc; Superhero comic books, strips, etc